A shadow bright and burning - Cluess, Jessica (Kingdom on fire ; book one., 2016)
"When her unusual powers mark her as the one destined to lead the war against the seven Ancients, Henrietta trains to become the first female sorcerer in centuries--though the true nature of her ability threatens to be revealed"--